PENGARUH PELATIHAN KERJA, MATERIAL HANDLING DAN PENERAPAN KESELAMATAN KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN GUDANG DI MITRA10 - Sutama Wisnu Dyatmika; , Kartika Agustien Cahyaningtyas (CV. Multi Kreasi Media, 2022)
As the main component in a company, human resources have an important role in carrying out various tasks or work that must be completed on time, so that it must always be considered by employees to always be serious when working. Companies must pay attention to the needs of employees while working, every company wants its employees to be able to work optimally and on time, the high challenges between companies make company managers and all employees have to be fast in completing their work. This study uses quantitative methods, population and samples which are all 31 employees of Gudang Mitra10. Test results obtained both partially and simultaneously that job training, material handling and the application of work safety have been proven to have an effect on the work effectiveness of warehouse employees at Mitra10.